Differences in the stability of the plasmids of Yersinia pestis cultures in vitro: impact on virulence - TC Leal-Balbino; NC Leal; CV Lopes; AMP de Almeida (Memorias do Instituto Oswaldo Cruz, 2004)
Plasmid and chromosomal genes encode determinants of virulence for Yersinia pestis, the causative agent of plague. However, in vitro, Y. pestis genome is very plastic and several changes have been described. To evaluate the alterations in the plasmid content of the cultures in vitro and the impact of the alterations to their pathogenicity, three Y. pestis isolates were submitted to serial subculture, analysis of the plasmid content, and testing for the presence of characteristic genes in each plasmid of colonies selected after subculture. Different results were obtained with each strain. The plasmid content of one of them was shown to be stable; no apparent alteration was produced through 32 subcultures. In the other two strains, several alterations were observed. LD50 in mice of the parental strains and the derived cultures with different plasmid content were compared. No changes in the virulence plasmid content could be specifically correlated with changes in the LD50.